Chemokine-like receptor 1 plays a critical role in modulating the regenerative and contractile properties of muscle tissue - Boesch, Julian; Pierrel, Eliane; Lambert, Christian; Doelemeyer, Arno; Kreider, Julie; Accart, Nathalie; Summermatter, Serge (Frontiers in Physiology, 2022)
Musculoskeletal diseases are a leading contributor to mobility disability worldwide. Since the majority of patients with musculoskeletal diseases present with associated muscle weakness, treatment approaches typically comprise an element of resistance training to restore physical strength. The health-promoting effects of resistance exercise are mediated via complex, multifarious mechanisms including modulation of systemic and local inflammation. Here we investigated whether targeted inhibition of the chemerin pathway, which largely controls inflammatory processes via chemokine-like receptor 1 (CMKLR1), can improve skeletal muscle function. Using genetically modified mice, we demonstrate that blockade of CMKLR1 transiently increases maximal strength during growth, but lastingly decreases strength endurance. In-depth analyses of the underlying long-term adaptations revealed microscopic alterations in the number of Pax7-positive satellite cells, as well as molecular changes in genes governing myogenesis and calcium handling. Taken together, these data provide evidence of a critical role for CMKLR1 in regulating skeletal muscle function by modulating the regenerative and contractile properties of muscle tissue. CMKLR1 antagonists are increasingly viewed as therapeutic modalities for a variety of diseases (e.g., psoriasis, metabolic disorders, and multiple sclerosis). Our findings thus have implications for the development of novel drug substances that aim at targeting the chemerin pathway for musculoskeletal or other diseases.